Knowledge and attitude towards "legalization of abortion law in Nepal " among adolescents studying in national academy for medical education, Kathmandu. - Das, Dipika (2006)
ABSTRACT: Every year about 40-50 million women resort to abortion, 20 million of which are considered unsafe. About 95 percent of all unsafe abortion takes place in developing countries. Unsafe abortion is responsible for 13 percent of all maternal deaths globally. Unsafe abortion is a major problem in Nepal contributing 50 percent of maternal mortality rate which is 539/100000 of which on e fifth are adolescent girls. Comparing with the other, adolescents face a higher risk of unintended pregnancies and unsafe abortion as a result of early marriage, lack of access and ability to use contraceptives and many form of sexual exploitation. Nepal have liberal abortion laws in order to promote maternal health and decrease maternal mortality rate, various studies have revealed that majority of the citizens are still unaware about the legalization and its legal aspects of abortion. This simple non-interventional descriptive study was undertaken to examine the knowledge and attitude towards legalization of abortion laws among adolescent group and to identify the effective way of communication to increase awareness regarding abortion legalization among citizens. The analysis is restricted to 100 adolescents. All most all of the respondents have heard about abortion but only half (58 percent) had exact information about abortion. Majority of respondents (81 percent) don't have knowledge about abortion law but bulk of them (82 percent) suggested abortion legalization should be promoted as it can decrease high maternal mortality rate 72 percent of the adolescents said abortion is women's reproductive right still remaining should know about it. Study revealed that effective means of communication to raise public awareness was disseminating through Radio/ T.V., Posters, pamphlets etc. As majority of the respondents were unaware about laws so focus should be given in creating awareness. Suggested effective means of communications should be used for awareness creation and beyond this, there is need of inclusion of knowledge regarding abortion to the most vulnerable group which is adolescents.